Eksperimentasi Model Pembelajaran Cooperative Learning (CL) dan Group Investigation (GI) ditinjau dari Kecerdasan Majemuk Siswa. - Nur Rohman (IKIP PGRI Bojonegoro, 2014)
The Experimentation of Cooperative Learning (CL) and Group Investigation (GI) Viewed from Multiple Intelligences. The purpose of this study is to manifest: (1) which learning model of the CL, GI or expository; (2) which multiple intelligences with the linguistic intelligence, logical-mathematials intelligence or spatial inteligence results in a better learning achievement. The research population was all of the students in Grade V of State Primary School first semester of 2013/2014 at Bojonegoro regency. The samples of the research were taken by using the stratified random sampling technique and then chosen three schools namely SD Negeri 1 Dander, SD Negeri 1 Ngulanan, dan SD Negeri 2 Ngumpakdalem. The hypotheses of the research were tested by using the two-way analysis of variance with unequal cells. The result of research were: (1) GI learning and Expository learning have better mathematics achievement than cooperative learning, meanwhile Expository learning have the same mathematics achievement as GI learning, (2) among students with linguistic intelligence, logical mathematical intelligence or visual spatial intelligence have the same mathematics achievement.Keywords: Clustering Technique, Writing Skill, Descriptive Text